2017
DOI: 10.1080/00028487.2017.1294542
|View full text |Cite
|
Sign up to set email alerts
|

Annual Movements of Acoustic‐Tagged White Sturgeon in the Lower Reaches of the Fraser River and its Tributaries

Abstract: Details of the spatial ecology of White Sturgeon Acipenser transmontanus in the lower Fraser River, British Columbia, are needed for habitat conservation, assessments of impacts from spatially delimited threats, and refinement of abundance estimation methods. The abundance of threatened lower Fraser River White Sturgeon is assessed annually using a Bayesian, closed‐population, mark–recapture model. If individuals make prolonged departures from the lower Fraser River, either into marine waters or a tributary, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
3
9
0
Order By: Relevance
“…These results were consistent with those of prior studies that found relatively low rates of angling‐related mortality for a similar species (0.01–4.0%, White Sturgeon, Robichaud et al. 2006; McLean et al. 2016).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results were consistent with those of prior studies that found relatively low rates of angling‐related mortality for a similar species (0.01–4.0%, White Sturgeon, Robichaud et al. 2006; McLean et al. 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Discard mortality rates that are associated with hook‐and‐line angling and simulated angling stress were low, 0.01% and 4%, respectively, for White Sturgeon Acipenser transmontanus (Robichaud et al. 2006; McLean et al. 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, tributaries may establish favourable habitat conditions that promote fish recruitment within altered main‐stem habitats (Pracheil, Pegg, & Mestl, ). The occurrence of movement between main‐stem and tributary habitats by fishes is well established (Koster, Dawson, O'Mahony, Moloney, & Crook, ; Nunn et al, ; Robichaud, English, & Nelson, ). Less understood, however, is the magnitude and direction of movement patterns as well as differences in population demographic parameters between main‐stem and tributary habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Primarily due to conservation concerns of this iconic fish, there have been numerous studies investigating the impact of C&R on WS populations ( McLean et al, 2016 , 2019 , 2020 ). Experimental work suggests that WS recover quickly from C&R angling in general and seldom experience mortality ( McLean et al, 2016 , 2019 , 2020 ), with an estimated direct mortality of angled fish <0.012% and 3-d postangling mortality rate of 2.6% ( Robichaud et al, 2006 ). Angling events can vary, with fight times ranging from seconds to >2 h with a median time of 5.78 min ( McLean et al, 2016 ), and WS are likely captured multiple times over their life.…”
Section: Introductionmentioning
confidence: 99%